2005
DOI: 10.1292/jvms.67.685
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Basement Membrane Zone Alteration of the Regenerated Laminar Region in Equine Chronic Laminitis

Abstract: ABSTRACT. Between the laminar epidermis and the laminar dermis of laminar region (LR) in equine foot, it can be observed the basement membrane zone (BMZ), which is composed of a basement membrane and its accompaniments like the hemidesmosome and anchoring fibril. Alteration in the BMZ in equine laminitis is possibly related with not only development but also recovery outcome and recurrence of this disease. However, there is little known about the structure of the BMZ during the recovery phase of this disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…It suggested that capability to form the hemidesmosomes in rLE might be lower than normal. This hypothesis is consistent with the previous report [10] in which existence of few hemidesmosomes were recognized in the BMZ. At current, we cannot propose any regulatory mechanism that can promote the type VII collagen and suppress the type XVII collagen, simultaneously in horse’s foot.…”
supporting
confidence: 94%
See 3 more Smart Citations
“…It suggested that capability to form the hemidesmosomes in rLE might be lower than normal. This hypothesis is consistent with the previous report [10] in which existence of few hemidesmosomes were recognized in the BMZ. At current, we cannot propose any regulatory mechanism that can promote the type VII collagen and suppress the type XVII collagen, simultaneously in horse’s foot.…”
supporting
confidence: 94%
“…The pathologic evidence at first stage is disconnection between the laminar epidermis (LE) and the laminar dermis (LD) resulted from basement membrane zone (BMZ) degradation [16,17,18]. While the detached epidermis structure loses vascular support and rapidly necrotizes, some keratinocytes attaching to the BMZ subsequently regenerate the LE [10, 16] and produce finally the ectopic white line tissue [9]. In this healing process, the regenerated laminar epidermis (rLE) could re-organize the BMZ in which the type VII and XVII collagens are included [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2004; Mobasheri et al . 2004) and delayed regeneration of anchoring filaments between keratinocytes and basement membrane (Kuwano et al . 2005) are features of acute and chronic laminitis, respectively, and because regenerations of hemidesmosomes and anchoring filaments must occur during healing, it is possible that glucocorticoids could further contribute to the severity of laminitis or delay remodelling of the hoof during recovery.…”
Section: How Might Glucocorticoids Predispose To the Development Of Lmentioning
confidence: 99%